Time-course of Serum Pro-inflammatory Cytokines and Chemokines Levels Observed in Granulomatosis with Polyangiitis: A Case Report - Kozu, Yutaka; Gon, Yusuhiro; Takano, Yuki; Noguchi, Takao; Hayashi, Shinichi; Kumasawa, Fumio; Mizumura, Kenji; Maruoka, Shuichiro; Hashimoto, Shu (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
A 77-year-old man visited our hospital with chief complaints of difficulty in hearing, nasal discharge and fever. The patients was diagnosed with otitis media, and his fever continued at approximately 38°C despite the administration of clarithromycin. After that, dyspnea on exertion developed and chest X-ray examination indicated multiple infiltrative shadows. PR3-ANCA levels were high (238-fold of the normal levels), and granulomatosis with polyangiitis (GPA) was diagnosed on the basis of clinical symptoms, laboratory results, and pathological findings. Thus, remission induction therapy was initiated with prednisolone and cyclophosphamide, following which symptoms and imaging findings rapidly improved. Blood concentrations of tumor necrosis factor-α, interleukin-8, and growth-related oncogene that had been measured since before treatment decreased over time with the improvement of lesions following treatment.